Effectiveness of Using E-learning at STEM-Based Sound-Wave Materials to Improve Collaboration Skills of High School Students - Rizki Nur Hidayah; Ketang Wiyono; Ismet Ismet (Universitas Lambung Mangkurat, 2022)
This study aims to see the effectiveness of STEM-based sound wave e-learning in improving the collaboration skills of high school students. The effectiveness test sample consisted of 30 SMAN 2 Palembang students selected with purposive sampling techniques. A collaborative skills rubric with three observers from Sriwijaya University's Master of Physics Education was the tool employed in this study. This study tested the effectiveness of using e-learning at STEM-Based Sound-wave materials to enhance students' established cooperation abilities. The t-test and N-Gain test are used for more reliable measurements to determine effectiveness. The t-test showed a significant increase in students' collaboration skills after being given treatment using e-learning at STEM-Based Sound-wave materials with tcount = 30.377, and the significance level was smaller than 0.05. N-Gain test showed that the e-learning at STEM-Based Sound-wave materials that had been developed significantly improved the collaboration skills of high school students with an N-Gain score of 0.68 in the medium category. The highest increase in the contribution aspect with an N-Gain score of 0.85, and the lowest in working with others with an N-Gain score of 0.62. These results showed that STEM-based sound wave e-learning is a good learning media option in physics learning to improve students' collaboration skills. It is recommended that further research be conducted on other 21st-century skills to find effective learning methods and media in responding to the challenges of life in the 21st century.